DISSOCIATION IN TMDs/HEADACHE/, TMDs/NON HEADACHE, AND NON TMDs/NON HEADACHE CONTROLS: HEALTH IMPLICATIONS IN THE GENERAL POPULATION - Tinoco, Molina; Santos, Zeila Coelho; Simião, Bruno Ricardo Huber; Aquilino, Raphael Navarro; Andrade, Douglas Oliveira de; Rank, Rise Consolação Iuata; Marquezan, Rogério Ferreira (REVISTA CEREUS, 2014)
Goal:Evaluate scores in dissociation in TMD and non TMD individuals. Methods:The Dissociative Experience Scale or DES was used in 196 TMDs and Headache, 39 TMDs no headache, 75 controls with headache and 38 controls with no headache individuals. Clinical examination, palpation of joint/muscles, criteria for TMDs and for differente headache types were used. Results: Mean DES scores in the TMD+HA, TMD - HA, Controls, Controls +HA and Controls - HA were about 17,7, 22,0 12, 6, 14, 8 and 10,5 respectively ( Tukey-Kramer ANOVA p<0.0001). The frequency of severe dissociation increased from the control no headache to the control + headache, to the TMD - headache and and to the TMD+headache subgroups (X-square for independence p=0,03, X-square for trends p=0,02). Conclusion: Higher scores in dissociation were observed in the subgroups presenting TMDs with and without headache. Controls no TMDs with headache presented higher scores as compared to Controls no TMDs amd mp headache. Headache in both TMDs and control individuals may increase the likelyhood of presenting higher scores in dissociation. Keywords: Dissociation. TMDs. Headaches.